Quality of Life and Treatment Satisfaction Among Patients on Long Term Oral Anticoagulant in A Developing Country - Tan, K.L.; Ng, Diana Leh-Ching; Gan, G.G.; Chai, C.S.; Chee, K.H. (Elsevier, 2019)
Background: Randomised phase III studies had proven the efficacy and safety profile of direct oral anticoagulant (DOAC) over warfarin in stroke and systemic embolism prevention for patients with atrial fibrillation (AF) and venous thromboembolism (VTE). Nevertheless, patients’ quality of life (QOL) and treatment satisfaction was not explored in these studies.